A rapid fuzzy optimisation approach to multiple sources water blending problem in water distribution systems - Peng, Wei; Mayorga, Rene V.; Imran, Syed (Urban water journal, 2012)
This paper proposes a Fuzzy Response Surface Optimisation (FRSO) approach for the water blending problem of multiple sources to maintain the water quality in water distribution systems. In the proposed approach, instead of the more precise and complicated nonlinear equations, the response surface models are used to describe the harmful reaction kinetics. The objectives of this study are to minimise the harmful reactions in the water network. A fuzzy linear programming using the min-operator approach is applied to handle the multiple objectives. Due to the FRSO only containing quadratic models, this approach is easy to apply and the optimisation is performed rapidly. Hence, the FRSO can be used to dynamically estimate the optimal blending ratios of water coming from multiple sources. Finally, a case study and two comparisons demonstrate the FRSO's advantages as to computational efficiency and simultaneous optimisation.